Shopee PayLater dalam Perspektif Al-Quran (Fatwa Majelis Ulama Indonesia) - Rifai, Ahmad; Hamidah, Tutik; Sofy, Malik (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2025)
Today's technological advances require humans to always go hand in hand with technology. One of them is buying and selling activities using an online system. This is considered easier and more efficient than offline transactions. One of the popular shopping applications in Indonesia today is Shopee. In practice, Shopee offers a feature called paylater. This research uses a qualitative descriptive research method to describe the practice of using Shopee Paylater loans from the perspective of Islamic law, while what is used is some research that has been done before. This research was conducted using a normative approach to evaluate the strengths and weaknesses of the issues under consideration. In this case whether the practice of using Shopee Paylater loans is Halal or Haram. Actually, it has been fulfilled by Shopee Paylater from the qardh contract both in terms of akid because of the mutual agreement between the two parties, the main object being traded can be trusted, and also shigat in the paylater system there is already a form of transaction confirmation between the two parties which is in accordance with the qardh contract. However, from another aspect, there are instruments that contain usury, namely in the practice of Shopee Paylater there are additions.